INDONESIA'S COMMUNICATION STRATEGY IN CTI-CFF COOPERATION IN SUPPORTING NATIONAL FOOD SECURITY - Salpidawati; Moh Rifaldi Akbar (PT. Jurnal Center Indonesia Publisher, 2025)
This article analyzes Indonesia's communication strategy in the multilateral Coral Triangle Initiative on Coral Reefs, Fisheries, and Food Security (CTI-CFF) cooperation, focusing on strategic communication approaches and environmentally-based digital diplomacy. The CTI-CFF is a crucial platform for Indonesia to build its image as a maritime leader and protector of the region's environment. This research employs a literature review and exploratory content analysis of scientific literature, policy documents, and social media content from relevant institutions, such as the Ministry of Maritime Affairs and Fisheries (MMAF) and the CTI-CFF Regional Secretariat. The findings indicate that Indonesia utilizes the CTI-CFF not only as a policy cooperation instrument but also as a strategic communication medium that combines the framing of environmental and food security issues. The